Comparison of Skin Staples Versus Prolene Sutures for Closure of Neck Dissection Incisions in Terms of Aesthetics and Wound Healing - Komal Akram, Uzair Bin Akhtar, Omer Sefvan Janjua, Rubbab Zahra, Tooba Ahmed, Maria Jabbar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare skin staples with prolene for closure of neck dissection incisions in terms of time for wound closure, pain on removal and aesthetic outcome. Study design and setting: Single blinded, prospective clinical study carried out at Sharif Medical and Dental College, Lahore from 19.04.2021 to 18.04.2022. Materials and methods: All healthy (ASA-I/II) patients requiring neck dissection were enrolled in the study. The patients were divided into two groups, incision in group A was closed with 3/0 vicryl and 5/0 prolene while incision in group B was closed using 3/0 vicryl and stainless-steel staples. Results: Total 140 patients were enrolled in the study with 70 patients in each group. In group A, 37 were males and 33 females while in group B, 43 were males and 27 females. The age in group A was 52.69+8.1 years while in group B, the age was 51.93+8.2 years. The mean time for wound closure in group A was 35.2+2.7 minutes while in group B it was 3.5+0.4 minutes. Pain on removal using VAS was 22.1+6.3 in group A while it was 21.8+5.5 in group B. In group A, 23 were excellent, 37 moderate and 10 poor while in group B, 27 were excellent, 38 moderate and 05 poor aesthetically. Overall, the results were statistically significant in terms of time of placement while they were statistically insignificant in terms of pain on removal and aesthetic outcome. Conclusion: The results of the study conclude that staples are a better modality for closing neck incisions after neck dissection as they are quicker to apply and yield similar outcomes as sutures. Keywords: Neck dissection, incision, closure, suturing.